MEMBANGUN MENTALITAS OPTIMIS DAN SABAR : TELAAH KONSEPTUAL DALAM AL-QUR’AN - Nadia Leila Rochima; Shofiyatul Hanik; Naila Rahma Haniyyah; Ana Rahmawati (CV. Adiba Aisha Amira, 2025)
This paper aims to explore the building of Optimistic and Patient mentality in the Qur'an which is important to study the meaning and significance of Building an optimistic and patient mentality is the most important thing in the elements to increase resilience for oneself and Spiritual well-being. The Qur'an emphasizes that the importance of these two attitudes is part of the guidance of life's journey and a form of obedience to Allah. In this conceptual study, it is found in Q.S Az-Zumar: 53, Allah commands his servants not to despair and have a strong mentality, and always provides a foundation of optimism and patience to be patient in all the problems we face so that humans always hope for His forgiveness and goodness. The purpose of this study is to foster optimism in a person who is guided. Grouping based on an approach that focuses on optimistic value assessment. Included in the interpretation of Q.S Al-Baqarah: 155 teaches that Allah does not burden someone beyond their abilities and has a mentality that can foster optimism and patience. Q.S. Al-Balad: 8, emphasizes that humans are created to face difficulties as part of their natural life, so they need patience in every process. This study aims to explore the meaning between optimism and patience in building a mentality according to the perspective of the Qur'an which teaches that with optimism and patience and still holding on to Allah's promise.